Does bank size and operational efficiency matters? an impact of financial gearing and asset management on Islamic bank’s performance in Pakistan - Khalil, Rashid; Khalil, Muhammad Azhar (CSRC Publishing, 2017)
Purpose: The persistent growth of Islamic banks has been the distinction of the Muslim world financial background in the 1980s and 1990s. Through a network that spans more than 62 countries and an asset base of more than $169 billion; Islamic banks are now performing a progressively more significant role in their particular economies. The core objective of this study is to find the impact of some of the key bank-specific factors (internal determinants) on the profitability of Islamic banks in Pakistan. Factors that opted in this study are bank size, operating efficiency, gearing ratio and asset management. Secondary data was obtained from 5 Islamic banks in Pakistan from year 2007 to 2015. The Ordinary Least Square (OLS) was used to analyze the empirical findings. The estimation results show that bank size significantly and positively influence the bank profitability while the asset management inversely affects the bank profitability. For future studies, it is recommended that more sample size and determinant factors can be included in determining the impact on bank's profitability.